ARCHDIOCESE OF JAKARTA: AN ANALYSIS OF ENTREPRENEURIAL PROACTIVENESS AND RISK TAKING - Wulandari, Respati (Catholic University Musi Charitas, 2024)
The Archdiocese of Jakarta, Indonesia's oldest diocese with a dynamic megapolitan population, must be proactive and willing to take risks in order to meet the needs of Catholics and fulfill its mission to the general public. With 37 parishes and a diverse parishioner population, Catholic priests encounter a variety of problems in carrying out the church's mission. A proactive approach and the willingness to take risks can boost organizational success. There has been no previous research on the Roman Catholic church with the concept of entrepreneurship, hence this study fills a research gap in terms of entrepreneurship theory and context in religious organizations. Using the framework of entrepreneurial proactiveness and entrepreneurial risk taking, in-depth interviews with 19 parish priests revealed that 19 parish priests applied entrepreneurial concepts to their ministry work. This study adds to the academic side of entrepreneurship in the context of religious non-profit organizations and offers practical guidance to NPO managers who are in a similar scenario.